Synthesis of graphene: potential carbon precursors and approaches - Yan, Yuxin; Nashath, Fathima Zahra; Chen, Sharon; Manickam, Sivakumar; Lim, Siew Shee; Zhao, Haitao; Lester, Edward; Wu, Tao; Pang, Cheng Heng (De Gruyter Open Ltd, 2020)
Graphene is an advanced carbon functional material with inherent unique properties that make it suitable for a wide range of applications. It can be synthesized through either the top–down approach involving delamination of graphitic materials or the bottom–up approach involving graphene assembly from smaller building units. Common top–down approaches are exfoliation and reduction while bottom–up approaches include chemical vapour deposition, epitaxial growth, and pyrolysis. A range of materials have been successfully used as precursors in various synthesis methods to derive graphene. This review analyses and discusses the suitability of conventional, plant- and animal-derived, chemical, and fossil precursors for graphene synthesis. Together with its associated technical feasibility and economic and environmental impacts, the quality of resultant graphene is critically assessed and discussed. After evaluating the parameters mentioned above, the most appropriate synthesis method for each precursor is identified. While graphite is currently the most common precursor for graphene synthesis, several other precursors have the potential to synthesize graphene of comparable, if not better, quality and yield. Thus, this review provides an overview and insights into identifying the potential of various carbon precursors for large-scale and commercial production of fit-for-purpose graphene for specific applications.